Effects of Berberine on glucolipid metabolism among dehydroepiandrosterone-induced rats of polycystic ovary syndrome with insulin-resistance - Li Li; Yao Xiao; Jiahe Zhou; Hui Mo; Xiaofang Li; Yuancheng Li; Youfeng Wang; Minglin Zhong (Heliyon, 2024)
Polycystic ovary syndrome (PCOS) is a set of endocrine disorder syndrome characterized by ovulation disorder. Increased insulin resistance (IR) and compensatory hyperinsulinemia play a vital role in the pathogenesis of PCOS. Therefore, insulin sensitizing agents have been studied in the treatment of PCOS. Berberine (BBR) has been proved to alleviate IR in patients with PCOS, but the mechanism remained unclear. This study was aimed to verify the regulatory mechanism of BBR on PCOS-IR rats. Firstly, we established a female rat PCOS-IR model induced by dehydroepiandrosterone (DHEA) and found that estrus cycle was disrupted in the PCOS-IR group, serum fasting insulin (FINS) level and the homeostasis model assessment of insulin resistance (HOMA-IR) index were significantly higher than normal control group. BBR treatment could recover estrous cycle, reduce abnormal serum hormone levels like luteotropic hormone (LH) and testosterone (T). Most importantly, BBR could concentration-dependently reduce serum FINS level in PCOS-IR rat model. Meanwhile, BBR may improve the abnormal lipid metabolism levels in PCOS-IR group by decreasing low density lipoprotein (LDL), total cholesterol (TC) and triglyceride (TG). Histological results showed that BBR can also protect normal histological structures of ovaries in PCOS-IR rats. Our results indicated that BBR plays a protective role in PCOS-IR, increasing insulin sensitivity, improving hyperandrogens and recovering abnormal blood lipids. Therefore, Our research provides novel insights for therapeutic treatment of BBR in patients with glucolipid metabolic disturbances.